2017
DOI: 10.1287/mnsc.2016.2547
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Nothing: Asymmetric Attention to Opportunity Costs Drives Intertemporal Decision Making

Abstract: T his paper proposes a novel account of impatience: People pay more attention to the opportunity costs of choosing larger, later rewards than to the opportunity costs of choosing smaller, sooner ones. Eight studies show that when the opportunity costs of choosing smaller, sooner rewards are subtly highlighted, people become more patient, whereas when the opportunity costs of choosing larger, later rewards are highlighted this has no effect. This pattern is robust to variations in the choice task, to the partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
1
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 77 publications
2
57
1
1
Order By: Relevance
“…Again, participants' choices were influenced by reminders of opportunity costs, in this case making them more patient. More recent research has shown that this effect is driven specifically by reminding participants of the future consequences—receiving $0 later (Read et al, ). Together, this research suggests that people tend to focus on information that is described and tend to neglect information that is not described.…”
Section: Opportunity Costsmentioning
confidence: 99%
“…Again, participants' choices were influenced by reminders of opportunity costs, in this case making them more patient. More recent research has shown that this effect is driven specifically by reminding participants of the future consequences—receiving $0 later (Read et al, ). Together, this research suggests that people tend to focus on information that is described and tend to neglect information that is not described.…”
Section: Opportunity Costsmentioning
confidence: 99%
“…To help individuals discount future rewards to a lesser degree, recent work (mostly in the financial decision‐making domain; Joshi & Fast, ; May & Monga, ) has developed interventions that direct attention toward the future, away from the present. For example, when consumers were reminded that they would get no financial reward in the future by choosing a smaller immediate financial reward (i.e., the hidden zero effect), they exhibited lower discounting rates (Magen, Dweck, & Gross, ; Read, Olivola, & Hardisty, ). Along similar lines, when employees considered the responsibility they had toward their future selves or were shown how much (or how little) money they would have in retirement based on their current saving behavior, consumers advocated saving more for retirement (Bryan & Hershfield, ; Goda, Manchester, & Sojourner, ; Goldstein, Hershfield, & Benartzi, ).…”
Section: Time Dichotomizedmentioning
confidence: 99%
“…Moreover, the rate at which a population shifts its focus from the past to the present over time (past time-horizon) also positively predicts economic output (Noguchi et al 2014). Finally, we echo Baumard's caution against drawing strong conclusions regarding the direction of the relationship between future orientation (or other time focus indices) and economic performance without appropriate, additional evidence, as each could plausibly affect the other: greater affluence could lead to people becoming more future-oriented; however, a greater focus on the future could also lead to greater affluence, by helping people consider the future consequences of their decisions (Read et al 2017), and thus maximize their long-term wealth.…”
Section: Different Kinds Of Environmental Harshness Impose Unique Infmentioning
confidence: 62%